Transposable Elements: Distribution, Polymorphism, and Climate Adaptation in Populus - Zhao, Yiyang; Li, Xian; Xie, Jianbo; Xu, Weijie; Chen, Sisi; Zhang, Xiang; Liu, Sijia; Wu, Jiadong; El-Kassaby, Yousry A.; Zhang, Deqiang (Frontiers in Plant Science, 2022)
Transposable elements (TEs) are a class of mobile genetic elements that make effects on shaping rapid phenotypic traits of adaptive significance. TE insertions are usually related to transcription changes of nearby genes, and thus may be subjected to purifying selection. Based on the available genome resources of Populus, we found that the composition of Helitron DNA family were highly variable and could directly influence the transcription of nearby gene expression, which are involving in stress-responsive, programmed cell death, and apoptosis pathway. Next, we indicated TEs are highly enriched in Populus trichocarpa compared with three other congeneric poplar species, especially located at untranslated regions (3'UTRs and 5'UTRs) and Helitron transposons, particularly 24-nt siRNA-targeted, are significantly associated with reduced gene expression. Additionally, we scanned a representative resequenced P. tomentosa population, and identified 9,680 polymorphic TEs loci. More importantly, we identified a Helitron transposon located at the 3'UTR, which could reduce WRKY18 expression level. Our results highlight the importance of TE insertion events, which could regulate gene expression and drive adaptive phenotypic variation in Populus.